Exploitation of Aspergillus terreus for the Production of Natural Statins - Mishal Subhan (Journal of Fungi, 2016)
The fungus Aspergillus (A.) terreus has dominated the biological production of the “blockbuster” drugs known as statins. The statins are a class of drugs that inhibit HMG-CoA reductase and lead to lower cholesterol production. The statins were initially discovered in fungi and for many years fungi were the sole source for the statins. At present, novel chemically synthesised statins are produced as inspired by the naturally occurring statin molecules. The isolation of the natural statins, compactin, mevastatin and lovastatin from A. terreus represents one of the great achievements of industrial microbiology. Here we review the discovery of statins, along with strategies that have been applied to scale up their production by A. terreus strains. The strategies encompass many of the techniques available in industrial microbiology and include the optimization of media and fermentation conditions, the improvement of strains through classical mutagenesis, induced genetic manipulation and the use of statistical design.